MODEL AKUNTABILITAS PENGELOLAAN KEUANGAN SEKOLAH MUHMMADIYAH (STUDI KASUS: SEKOLAH MUHAMMADIYAH DI MALANG RAYA) - Sawalni Sawalni (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
The results of research that researchers have done about the financial management model of the Muhammadiyah Malang Raya school, it can be concluded that: there is a lack of uniformity in the financial management of the Muhammadiyah Malang Raya school. So the researchers concluded that there were no standards in the financial management of the Muhammadiyah Malang Raya school. in general there are many problems in achieving accountability standards in Muhammadiyah Malang Raya schools such as: in general schools do not have financial management guidelines from the Muhammadiyah association, do not have a request and disbursement mechanism and do not have a written procurement mechanism. The preparation of the budget does not involve the DIKDASMEN Assembly as the owner of the school foundation. Lack of clarity in organizing the Muhammadiyah Malang Raya school. Supervision conducted by the DIKDASMEN assembly as the owner is not optimal, whereas the DIKDASMEN Assembly is more for the recipient of the report. So that schools manage school finances in accordance with regulations obtained from outside such as the government. In reporting there are no clear rules on where to submit and there are still books that do not have proof of receipt and disbursement of funds and are incomplete